Mapping Sustainability Risks and Opportunities in the Patchouli Agribusiness System Based on the Triple Bottom Line - Irmawati Irmawati; Adiputra Rahman; Mawar Mawar; Hajriani Kadir; Nayla Naesyla (Jurnal Publikasi Ilmu Manajemen, 2026)
This study aims to analyze the sustainability level of patchouli agribusiness systems using the Triple Bottom Line (TBL) framework and to map the risks and opportunities that influence their sustainability, as well as to formulate development strategies through SWOT analysis. The research was conducted in Patambanua Village, Bulo District, Polewali Mandar Regency, involving 100 respondents comprising farmers, distillers, traders, and stakeholders, selected using purposive sampling. Data were collected through questionnaires, semi-structured interviews, and field observations, then analyzed using sustainability index, risk-opportunity mapping, and SWOT analysis. Results show that the overall TBL sustainability index reached 3.44 (moderate category), with the social dimension scoring highest (3.51) and the environmental dimension lowest (3.38). Risk mapping identified seven high-risk factors, with limited market access as the highest risk (score 17.52), followed by high production costs (17.47) and labor shortages (17.35). Opportunity mapping found that farmer institutional strengthening (17.22), government support (16.94), and new technology adoption (16.91) are the main strategic opportunities. SWOT analysis resulted in five priority strategies: (1) strengthening farmer institutions and market access, (2) adopting modern cultivation and distillation technology, (3) improving capital access and production efficiency, (4) sustainable distillation waste management, and (5) developing derivative products and market diversification. These findings provide an evidence-based foundation for the development of sustainable patchouli agribusiness policies in Polewali Mandar.